High-Dose Isoniazid Therapy for Isoniazid-Resistant Murine Mycobacterium tuberculosis Infection - Cynamon, M. H. (American Society for Microbiology, 1999)
The use of isoniazid (INH) for the treatment of INH-resistant Mycobacterium tuberculosis infection has been controversial. The purpose of the present studies was to determine if there is a dose response with INH for INH-susceptible M. tuberculosis Erdman (ATCC 35801), and whether high-dose INH (100 mg/kg of body weight) was more effective than standard-dose INH (25 mg/kg) for therapy of tuberculosis infections caused by INH-resistant mutants of M. tuberculosis Erdman. Six-week-old CD-1 mice were infected with approximately 10(7) viable mycobacteria. Early control groups of infected but untreated mice were euthanized by CO(2) inhalation 1 week later when treatment was initiated. INH (25, 50, 75, and 100 mg/kg) was given by gavage 5 days/week for 4 weeks. Late control groups of untreated mice and treated mice were sacrificed 2 days after the last dose of drug. Spleens and right lungs were removed aseptically and homogenized, and viable cell counts were determined by titration on 7H10 agar plates. In the next study, INH at 100 mg/kg was compared to INH at 25 mg/kg against an isogenic mutant of M. tuberculosis Erdman (INH MIC, 2 μg/ml) and the parent strain. This mutant was found to have a mutation in the KatG protein (Phe to Leu at position 183). In the first study, there was no dose response with increasing doses of INH. In the second study, there was no significant difference between the reduction of viable cell counts for mice treated with INH at 100 mg/kg and that for mice treated with INH at 25 mg/kg (parent or INH-resistant mutant). These preliminary results suggest that INH may be useful in combination therapy of M. tuberculosis infections caused by low-level INH-resistant organisms (INH MICs, 0.2 to 5 μg/ml) and that higher doses of INH are unlikely to be more efficacious than the standard 300-mg/day dose.